Etika Ibn Miskawaih dan Implikasinya bagi Masyarakat Muslim - Yunita Kurniati (Matan : Journal of Islam and Muslim Society, 2021)
Abstract: This paper discusses the ethics in Ibn Miskawaih's thought and its implications for Muslim societies. This is a library research. The data has been collected through the documentation method with the primary source is Ibn Miskawaih's work, while the secondary source is the other sources related to Ibn Miskawaih's thoughts. The data were analyzed by a descriptive method. The results showed that there were three main problems discussed in Ibn Miskawaih's ethics, namely goodness, happiness, and virtue. Happiness is the main thing in his thinking. The implication of his thought for the Muslim community is to awaken the Muslim community to be able to change themselves for the better life, since the bad human deed is not a character, but can still be changed through practicing.